Upaya Isteri dalam Mencari Nafkah Keluarga dalam Perspektif Maqashid Al- Syariah: (Studi Kasus di Desa Soko Kabupaten Tuban Jawa Timur) - Munir Munir; Farida Isroani (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2024)
Providing a living in Islam is the responsibility of a husband. The provisions on the husband's obligation to provide maintenance give rise to new problems regarding the wife's implementation of work to meet the family's needs. The aim of this research is to evaluate the sharia values ​​that exist in the case of women working for a living. The problem in this research is how women work to earn a living for their family's needs in the view of maqashid sharia, what are the factors that influence women who work to earn a living, including: the husband's illness, helping prepare the family's future and the factor of helping the husband's income to meet family needs and this can be justified by referring to maqashid sharia. This research uses descriptive research methods using a qualitative descriptive analysis approach. The results of this research are that in a family the husband and wife can play the same role in the family, the wife plays the role of breadwinner for the family due to various factors that cause the family's needs to not be met.